The socialization process of children in the latency period in a school in Maracanaú-Ceará (Research, Society and Development, 2020)
The present work is the result of the observation of three children aged 8 years, in the school context in the municipality of Maracanaú- Ceará, carried out between September 30 and October 17, 2019. The children, at the time of observation, were inserted in a regular class of 3rd year of Elementary School in the morning shift where there were thirty students regularly enrolled. The study aims to describe the behavior observed in the field, establishing pertinent relationships between what the literature brings regarding the process of socialization of children in the latency period, also reflecting on the role of the school in this context. Therefore, the method used was qualitative research using non-participatory observation as a technique of social investigation. As a result, it was noticed that the vast majority of children in this class have problematic behaviors that reflect on their learning. This leads us to think about the use of art in the school context as a possible measure to be taken to minimize this problem in view of the important role that the school has in the socialization process.